2006
DOI: 10.3354/meps314077
|View full text |Cite
|
Sign up to set email alerts
|

Down-mixing of phytoplankton above filter-feeding mussels—interplay between water flow and biomixing

Abstract: Filter-feeding bivalves may have a pronounced grazing impact on the phytoplankton biomass in many shallow marine areas. The blue mussel Mytilus edulis, which lives in dense beds, can filter more than 100 m 3 m -2 d -1, but the grazing impact is highly influenced by hydrodynamic processes. Without externally generated currents or turbulent mixing, only a thin layer of near-bottom water would be subject to the down-mixing that causes an important supply of food to the mussels. Here, food-depleted jets of water e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 53 publications
1
28
0
1
Order By: Relevance
“…Under optimal conditions, suspensionfeeding bivalves filter the ambient water at a maximum rate, but under suboptimal environmental conditions, including low or very high concentrations of algal cells, the valve gape is reduced, and the mantle edges retracted [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. However, it has for a long time been a matter of discussion whether the filtration rate in suspension-feeding bivalves is physiologically regulated [14][15][16][17][18][19][20][21][22][23], or if it should be conceived as a basically autonomous process [2,5,[24][25][26][27].…”
Section: Physiological Regulation Of Feedingmentioning
confidence: 99%
“…Under optimal conditions, suspensionfeeding bivalves filter the ambient water at a maximum rate, but under suboptimal environmental conditions, including low or very high concentrations of algal cells, the valve gape is reduced, and the mantle edges retracted [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. However, it has for a long time been a matter of discussion whether the filtration rate in suspension-feeding bivalves is physiologically regulated [14][15][16][17][18][19][20][21][22][23], or if it should be conceived as a basically autonomous process [2,5,[24][25][26][27].…”
Section: Physiological Regulation Of Feedingmentioning
confidence: 99%
“…Z. ma rina beds are suitable habitats for M. edulis, providing substrate for settlement, shelter from predators and high sedimentation of particles (Reusch 1998, Gacia et al 2002, Bologna et al 2005. Being an efficient suspension feeder, M. edulis is among the most important regulators of suspended materials in the coastal zone, and is able to filter the water up to 1 m above the mussel bed (Prins et al 1998, Dolmer 2000, Lassen et al 2006. Furthermore, M. edulis ex cretes a large part of ingested material as faeces or pseudofaeces (Kautsky & Evans 1987, Hartstein & Rowden 2004, which can enhance nutrient availability in the sediments.…”
Section: Introductionmentioning
confidence: 99%
“…The dynamics of exhalent jets are more complicated to resolve since they can either increase mixing (biomixing) in the logarithmic boundary layer (O'Riordan et al 1995, Larsen & Riisgaard 1997 or increase refiltration, depending on bivalve density, siphon height, filtration velocity and friction velocity (O'Riordan et al 1995, Jonsson et al 2005. A recent study showed that the exhalent jets above a 2 m-long, dense bed of Mytilus edulis increased friction velocity by 56% at low flow speeds of ~0.04 m s -1 and hence increased turbulent mixing (Lassen et al 2006). Increased turbulent mixing above the mussel bed due to roughness and biomixing was included in the applied physical water column model by increasing the roughness length by a factor of 10 in comparison with the sand bed.…”
Section: Turbulent Mixingmentioning
confidence: 99%